2012
DOI: 10.1152/ajpendo.00605.2011
|View full text |Cite
|
Sign up to set email alerts
|

The Rab-GTPase-activating protein TBC1D1 regulates skeletal muscle glucose metabolism

Abstract: The Rab-GTPase-activating protein TBC1D1 has emerged as a novel candidate involved in metabolic regulation. Our aim was to determine whether TBC1D1 is involved in insulin as well as energy-sensing signals controlling skeletal muscle metabolism. TBC1D1-deficient congenic B6.SJL-Nob1.10 (Nob1.10(SJL)) and wild-type littermates were studied. Glucose and insulin tolerance, glucose utilization, hepatic glucose production, and tissue-specific insulin-mediated glucose uptake were determined. The effect of insulin, AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
89
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(109 citation statements)
references
References 37 publications
(64 reference statements)
18
89
2
Order By: Relevance
“…Previous studies of isolated L6 muscle cells and 3L3-L1 adipocytes demonstrated that ablation of either Tbc1d1 or Tbc1d4, or overexpression of mutated proteins, resulted in reduced insulin-stimulated translocation of GLUT4 (20)(21)(22). However, knockout mice lacking either Tbc1d1 (15,23) or Tbc1d4 (14,24) displayed only tissue-specific impairments of insulin-stimulated glucose uptake and rather minor alterations in glycemic control, indicating a substantial level of redundant expression and signaling.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies of isolated L6 muscle cells and 3L3-L1 adipocytes demonstrated that ablation of either Tbc1d1 or Tbc1d4, or overexpression of mutated proteins, resulted in reduced insulin-stimulated translocation of GLUT4 (20)(21)(22). However, knockout mice lacking either Tbc1d1 (15,23) or Tbc1d4 (14,24) displayed only tissue-specific impairments of insulin-stimulated glucose uptake and rather minor alterations in glycemic control, indicating a substantial level of redundant expression and signaling.…”
mentioning
confidence: 98%
“…In humans, mutations in TBC1D4 (R3633) and TBC1D1 (R125W) have been linked to severe postprandial hyperinsulinemia and obesity, respectively (11)(12)(13). TBC1D4 is found mainly in the heart, adipose tissue, and oxidative muscle fibers, whereas TBC1D1 is predominantly expressed in glycolytic skeletal muscle and is nearly absent from fat tissue (10,14,15). Both TBC1D1 and TBC1D4 display a similar domain architecture that includes two N-terminal phosphotyrosine-binding domains and a Rab-GTPaseactivating (GAP) domain.…”
mentioning
confidence: 99%
“…These mice show no change in body weight or reduced body weight; reduced glucose uptake into isolated white muscle in response to various agonists, including insulin, contraction, or AICAR, an AMPK agonist; and increased fatty acid oxidation at the whole-body level and in muscle. In general, no defect in whole-body insulinmediated glucose metabolism was found (22)(23)(24)(25).…”
Section: /2mentioning
confidence: 94%
“…Several mouse models with reduced TBC1D1 expression have been described, including a congenic model that contains a locus from the Swiss Jim Lambert strain, and a gene trap knockout (22)(23)(24)(25). These mice show no change in body weight or reduced body weight; reduced glucose uptake into isolated white muscle in response to various agonists, including insulin, contraction, or AICAR, an AMPK agonist; and increased fatty acid oxidation at the whole-body level and in muscle.…”
Section: /2mentioning
confidence: 99%
“…TBC1D1 in regulation of glucose metabolism in skeletal muscle in response to contraction and insulin stimuli , Pehmoller et al 2009, Szekeres et al 2012). …”
Section: Convergent Mechanisms Of Glucose Uptake: Role Of As160 and Tmentioning
confidence: 99%